Comparison of Intravenous Ramosetron and Ondansetron for Prevention of Postoperative Nausea and Vomiting in Patients Undergoing Laparoscopic Surgeries - Fating, Dnyaneshwar Ramaji; Sonawane, Vinay P.; Jatale, Amol (Academia Anesthesiologica International, 2018)
Background: Nausea and vomiting are distressing symptoms after laparoscopic surgeries. Number of drugs is used but none is devoid of side effects. Introduction of 5-HT3 receptors antagonists heralded the major advance in the treatment of postoperative nausea and vomiting. Hence search for ideal new 5-HT3 receptors antagonists goes on. Aim: The aim of the present study was to compare the efficacy of intravenous ramosetron and ondansetron for prevention of postoperative nausea and vomiting in patients undergoing laparoscopic surgeries. Subjects and Methods: 144 patients of ASA physical status I and II, posted for elective laparoscopic surgeries under general anaesthesia were included in this prospective randomized study. Patients were randomly allocated into two groups to receive either injection Ramosetron 0.3 mg or injection Ondansetron 4 mg intravenously. Incidence of nausea, vomiting or both, need of rescue antiemetic and complete response were recorded for 24 hrs. Data was analyzed statistically. Results: Overall incidence of PONV was observed in 15.27% patients in group R and 36.11% in group O. Rescue antiemetic was used in 5.55% patients in group R compared to 22.22% in group O. Complete response was found in 84.74% patients of group R and 63.88% of group O. Conclusion: Intravenous Ramosetron with dose of 0.3 mg appears to be a promising drug for prevention of postoperative nausea and vomiting in laparoscopic surgery under general anaesthesia.